Régimen escópico colonial: mural crítica cultural del “la medicina en el cauca” de belisario gómez - García Quintero, Felipe (CALLE14: revista de investigación en el campo del arte, 2011)
This essay is a critical reflection on the contemporary colonial statute in Popayan (Colombia). Approaching the artistic devices of a recent mural, it inquires about the iconic representation in the construction of an urban cultural identity, beyond the aesthetic valuation or the curatorial purpose of art, which aren’t the issues dealt with in this visual interpretation exercise. The purpose of the essay is to initiate a critical dialogue with the work about the political meaning of representing a cultural being. For this intent, the popular sensorium and the perception of the expert are put on hold, because this valuation exercise is subjective in nature and doesn’t involve anything more than the judgment of the individual, and as such the aesthetic discussion is displaced to the political horizon to determine the roads that identity takes on, and the meanings of this identity in an urban context, all the while thinking about the contemporary colonial statue as a device of cultural power.